Kontestasi Aktor dan Model Kolaboratif Pemberdayaan Orang Rimba di Taman Nasional Bukit Duabelas Provinsi Jambi - Muchlis, Fuad; Sardi, Idris (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
The empowerment of the Orang Rimba aims to enable them to get out of their marginal condition due to the development pattern that has not been on their side so far. This study aims to analyze how the contestation of various ideologies underlie various actors empowering the Orang Rimba and to formulate a collaborative model between actors in empowerment that can answer the needs of the Orang Rimba. The research uses a case study approach and is analyzed qualitatively. The results show that the empowerment of Orang Rimba is interpreted by the state as